Digital forensics with Kali Linux perform data acquisition, data recovery, network forensics, and malware analysis with Kali Linux 2019.x - Parasram, Shiva V. N. (Packt Publishing, 2020)
Kali Linux is a Linux-based distribution that's widely used for penetration testing and digital forensics. It has a wide range of tools to help for digital forensics investigations and incident response mechanisms. This updated second edition of Digital Forensics with Kali Linux covers the latest version of Kali Linux and The Sleuth Kit. You'll get to grips with modern techniques for analysis, extraction, and reporting using advanced tools such as FTK Imager, hex editor, and Axiom. Updated to cover digital forensics basics and advancements in the world of modern forensics, this book will also delve into the domain of operating systems. Progressing through the chapters, you'll explore various formats for file storage, including secret hiding places unseen by the end user or even the operating system. The book will also show you how to create forensic images of data and maintain integrity using hashing tools. Finally, you'll cover advanced topics such as autopsies and acquiring investigation data from networks, operating system memory, and quantum cryptography. By the end of this book, you'll have gained hands-on experience of implementing all the pillars of digital forensics: acquisition, extraction, analysis, and presentation, all using Kali Linux tools.